The Jigsaw Learning Model to Promote Engagement in the English Language Classroom: A Teacher’s Reflection - Suwartono, Tono; Romdona, Yaomal (Acta Pedagogia Asiana, 2024)
Learning activities employing the lecture model have induced boredom among students and resulted in poor participation in the classroom, including in the English as a foreign language class. Low student participation in classrooms may impede the development of their skills. The jigsaw cooperative learning model provides an opportunity for students to collaborate and actively participate. This collaborative action research aims to assist students in addressing engagement issues in English lessons through the jigsaw cooperative learning model. The collaborative action research involved a cohort of 36 primary school students, comprising 20 females and 16 males, in the city of Purwokerto, Indonesia. Data was collected through observation, and the observational data obtained were then analyzed using descriptive statistics. After three cycles, student engagement increased from 56% (baseline) to 65.56%, 75.56%, and 79.44%, respectively. The desired criteria for intervention success (75%) were met in cycle 2, leading to the conclusion of the investigation in cycle 3. Based on the results, it can be inferred that the adoption of the jigsaw learning model has effectively enhanced student engagement in the English language class. Practical implications of the study are then presented.